Unique Features of a Pseudomonas aeruginosa α2-Macroglobulin Homolog - Robert-Genthon, Mylène (American Society of Microbiology, 2013)
Human pathogens frequently use protein mimicry to manipulate host cells in order to promote their survival. Here we show that the opportunistic pathogen Pseudomonas aeruginosa synthesizes a structural homolog of the human α2-macroglobulin, a large-spectrum protease inhibitor and important player of innate immunity. Small-angle X-ray scattering analysis demonstrated that the fold of P. aeruginosa MagD (PA4489) is similar to that of the human macroglobulin and undergoes a conformational modification upon binding of human neutrophil elastase. MagD synthesis is under the control of a general virulence regulatory pathway including the inner membrane sensor RetS and the RNA-binding protein RsmA, and MagD undergoes cleavage from a 165-kDa to a 100-kDa form in all clinical isolates tested. Fractionation and immunoprecipitation experiments showed that MagD is translocated to the bacterial periplasm and resides within the inner membrane in a complex with three other molecular partners, MagA, MagB, and MagF, all of them encoded by the same six-gene genetic element. Inactivation of the whole 10-kb operon on the PAO1 genome resulted in mislocalization of uncleaved, in trans-provided MagD as well as its rapid degradation. Thus, pathogenic bacteria have acquired a homolog of human macroglobulin that plays roles in host-pathogen interactions potentially through recognition of host proteases and/or antimicrobial peptides; it is thus essential for bacterial defense.